1991
DOI: 10.1182/blood.v77.6.1383.bloodjournal7761383
|View full text |Cite
|
Sign up to set email alerts
|

Single-unit transfusions of RBC enzymatically converted from group B to group O to A and O normal volunteers

Abstract: Full-unit transfusions of RBC enzymatically converted from group B to group O by treatment with alpha-galactosidase (ECO RBC) to group O and A normal healthy individuals exhibit excellent in vivo survival times (24-hour survival 95.1% +/- 2.3%, T50 36.9 +/- 4.6 days). These results confirm our earlier findings describing ECO RBC in vitro viability and normal in vivo survival time after small-volume infusions. No significant increase in pretransfusion anti-B titer or score is observed in either group O or A sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Overall, the transfusions of ECO RBCs appeared safe and effective; there were no acute transfusion reactions or evidence of hemolysis, and chromium survival studies showed that the lifespans of the transfused ECO and group O RBCs were equal. However, a number of in vitro serologic abnormalities were noted, which were similar to observations in the previous studies of ECO RBC transfusions to normal volunteers 4,5 . Five of 19 patients who received ECO RBCs had significant increases in anti‐B titers, and 2 of these patients had incompatible antiglobulin crossmatches with ECO RBCs 7 .…”
Section: Enzymatically Converted Group O Cellssupporting
confidence: 80%
See 2 more Smart Citations
“…Overall, the transfusions of ECO RBCs appeared safe and effective; there were no acute transfusion reactions or evidence of hemolysis, and chromium survival studies showed that the lifespans of the transfused ECO and group O RBCs were equal. However, a number of in vitro serologic abnormalities were noted, which were similar to observations in the previous studies of ECO RBC transfusions to normal volunteers 4,5 . Five of 19 patients who received ECO RBCs had significant increases in anti‐B titers, and 2 of these patients had incompatible antiglobulin crossmatches with ECO RBCs 7 .…”
Section: Enzymatically Converted Group O Cellssupporting
confidence: 80%
“…Pioneering studies by the late Jack Goldstein and colleagues 3 at the New York Blood Center demonstrated that this process of enzymatic conversion of group B RBCs to group O could be carried out with the enzyme coffee bean α‐galactosidase under conditions that leave the RBCs physically and functionally intact and suitable for transfusion. Studies in group O or group A volunteer recipients showed that these enzymatically converted group O (ECO) cells functioned essentially identically to group O RBCs; there was no evidence of acute transfusion reactions or hemolysis, and RBC survival in the recipients was normal 4 . Multi‐unit or second transfusions were also well tolerated 5,6 .…”
Section: Enzymatically Converted Group O Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their studies of transfusions of enzyme-treated group B RBCs to allogeneic recipients, Lenny et al1*'4. 15 and Goldstein et a1.I6 treated group B RBCs with a coffee bean a-galactosidase at sufficiently high concentrations to abolish hemagglutination with B antisera within 2.5 hours of incubation. They demonstrated that RBCs so treated survived normally in blood group A and 0 recipients, including those receiving repeated transfusions of enzyme-treated group B RBCS.','~.…”
Section: Change In Expression Of Surface Antigens On A2 Rbcs Duringmentioning
confidence: 99%
“…These studies demonstrated survival of ECO-RBCs in the blood stream and absence of the usual early clinical signs of haemolytic immune reaction. A few years later the same group reported transfusion of one to two full units (200-400 ml) of ECO-RBC with no particular side effects (Lenny et al, 1991(Lenny et al, , 1995. Kruskall et al (2000) reported a similar trial involving transfusion of two units of ECO-RBC in a cohort of 21 A patients presenting with various diseases [solid tumours, leukaemia, human immunodeficiency virus (HIV) infection].…”
Section: Enzymatic Conversion Of a And B Antigens: The Eco-rbc Conceptmentioning
confidence: 99%